“Absolutely sort of normal”: the common origins of the war on poverty at home and abroad, 1961-1965 - Aksamit, Daniel Victor (Kansas State University, 2014)
Scholars identify the early 1960s as the moment when Americans rediscovered poverty – as the time when Presidents, policymakers, and the public shifted their attention away from celebrating the affluence of the 1950s and toward directly helping poor people within the culture of poverty through major federal programs such as the Peace Corps and Job Corps. This dissertation argues that this moment should not be viewed as a rediscovery of poverty by Americans. Rather, it should be viewed as a paradigm shift that conceptually unified the understanding of both foreign and domestic privation within the concept of a culture of poverty. A culture of poverty equally hindered poor people all around the world, resulting in widespread illiteracy in India and juvenile delinquency in Indianapolis. Policymakers defined poverty less by employment rate or location (rural poverty in Ghana versus inner-city poverty in New York) and more by the cultural values of the poor people (apathy toward change, disdain for education, lack of planning for the future, and desire for immediate gratification). In a sense, the poor person who lived in the Philippines and the one who lived in Philadelphia became one. They suffered from the same cultural limitations and could be helped through the same remedy. There were not just similarities between programs to alleviate poverty in either the Third World or America; the two became one in the mid-1960s. Makers of policy in the War on Poverty understood all poverty around the world as identical and approached it with the same remedy. President John Kennedy inspired the paradigm shift. After reading about the culture of poverty in Dwight Macdonald’s review of Michael Harrington’s book The Other America: Poverty in the United States, Kennedy began to bring together experts within a new mentality to discuss a program to end poverty. The experts had been working for separate programs that focused on seemingly disparate issues—juvenile delinquency, poverty in New England, and Third World development—but they now realized that they were all working on the same problem, namely, the culture of poverty. The understanding that cultural values created poverty led them to unify their programs and approaches as they created the War on Poverty in 1964. The discovery was not the beginning of national attention on poverty but a culmination that brought together prominent people, ideas, and programs already in existence within a new paradigm.
Keywords: American History; Poverty; War on poverty; Culture of poverty; 1960s; Kennedy, John F; American History (0337)